Sexually dimorphic nuclei in the spinal cord control male sexual functions - Sakamoto, Hirotaka (Frontiers in Neuroscience, 2014)
Lower spinal cord injuries frequently cause sexual dysfunction in men, including erectile dysfunction and an ejaculation disorder. This indicates that the important neural centers for male sexual function are located within the lower spinal cord. It is interesting that the lumbar spinal segments contain several neural circuits, showing a clear sexually dimorphism that, in association with neural circuits of the thoracic and sacral spinal cord, are critical in expressing penile reflexes during sexual behavior. To date, many sex differences in the spinal cord have been discovered. Interestingly, most of these are male dominant. Substantial evidence of sexually dimorphic neural circuits in the spinal cord have been reported in many animal models, but major issues remain unknown. For example, it is not known how the different circuits cooperatively function during male sexual behavior. In this review, therefore, the anatomical and functional significance of the sexually dimorphic nuclei in the spinal cord corresponding to the expression of male sexual behavior is discussed.